Consumption Frequency of Fruit Juices and Sweetened Beverages: Differences Related to Age, Gender and the Prevalence of Overweight Among Polish Adolescents - Wuenstel Justyna W.; Wądołowska Lidia; Słowińska Małgorzata A.; Niedźwiedzka Ewa; Kowalkowska Joanna; Antoniak Lidia (Polish Journal of Food and Nutrition Sciences)
The aim of the study was to analyse the differences in the consumption frequency of fruit juices and sweetened beverages according to gender, age and the prevalence of overweight. The study involved 1,700 adolescents aged 13-19 from north-eastern Poland. The frequencies of juices and beverages consumption are presented in 5 categories: from less than once a week to daily. On the basis of measurements of body weight and height the relative body mass (rBMI) is calculated, using standardization by Cole. The study showed that 77.8% of the sample had normal weight and 16.9% were overweight. Girls more often consumed fruit juices than boys and sweetened beverages less often. Girls with age drank less frequently fruit juices and sweetened beverages. Among boys, only the frequency of fruit juice consumption decreased with age. Daily consumption of sweetened beverages among young people increased the risk of being overweight by more than 60% compared to young people consuming them once a week. The frequency of consumption of fruit juices and sweetened beverages was more strongly related to age and sex than to body mass. The prevalence of overweight among adolescents was associated with the frequency of sweetened beverage consumption, but not with the frequency of fruit juice consumption.